The role of fiscal policy in Iraq after 2003 in diversifying sources of income: an analytical study: Peran kebijakan fiskal di Irak setelah 2003 dalam diversifikasi sumber pendapatan: sebuah studi analitis - Tareq Abbas Jasim (Academia Open, 2026)
General Background: Resource-dependent economies face persistent challenges in achieving sustainable growth and economic diversification. Specific Background: Iraq’s economy is characterized by heavy reliance on oil revenues, weak non-oil sectors, and fiscal imbalances that constrain long-term development. Knowledge Gap: Despite numerous fiscal reforms, limited evidence explains why diversification outcomes remain weak within Iraq’s public revenue and expenditure framework. Aims: This study examines fiscal policy instruments, public revenue composition, and their role in supporting economic diversification in Iraq. Results: The findings indicate that oil revenues dominate total public revenues, while non-oil sectors contribute marginally to gross domestic product, reflecting structural imbalances and inefficient public spending patterns. Novelty: The study provides an integrated analysis of fiscal, sectoral, and institutional factors shaping diversification outcomes in the Iraqi economy. Implications: The results highlight the need for balanced fiscal policies and stronger support for productive sectors to reduce oil dependency and promote economic stability. Keywords: Fiscal Policy, Economic Diversification, Public Revenues, Oil Dependency, Iraqi Economy Key Findings Highlights: Public revenues in Iraq remain highly concentrated in the oil sector. Non-oil productive sectors contribute weakly to economic structure. Fiscal imbalances limit progress toward diversification goals.